Classroom Techniques Used in the Teaching of English at SMP Negeri 1 Sawit Boyolali: A Naturalistic Study - Kurniliawati, Umi Nur; , Prof. Dr. Endang Fauziati, M. Hum; , Nur hidayat, M. Pd (2016)
The purpose of this research is to observing the teaching-learning process at SMP Negeri 1 Sawit, Boyolali. This study is carried out to describe types of classroom technique used in the teaching English, purposes in using each technique, teacher's and student's role, and instructinal material used at SMP Negeri 1 Sawit Boyolali. The kinds of this research is describtive qualitative research especially naturalistic study in analyzing the data. Methods of collecting data in this research are observation, interview and document. In this research, the data are taken from the English teachers attitude, interview students and English teachers. The finding of the study shows that there are some classroom techniques implemented by English teachers at SMP Negeri 1 Sawit such as: answering question, checking, correction, discussion, drilling, grouping, individual task, listening to music, picture describing, presentation, question and answer, questioning, reading aloud, repetition, role play, and translation. The teachers have roles as facilitator, motivator, observer, manager, model, counselor, controller, and evaluator. The students have roles as a member of a group, as tutor of other learners, as negotiator, as subject, and as monitor and evaluator of their own learning progress. There are some materials used by English teachers, such as: textbook, workbook, dictionary, photocopy exercises, powerpoint on LCD, audio like song, and videos from youtube. The conclusion of this research is that English teachers at SMP N 1 Sawit used various classroom techniques which can improve the students' ability in English skill. Various techniques can make the students interested in English teaching-learning process. It does not make the class monotonous. The students become more active and creative. Based on the results, apparently, classroom techniques used by the teachers have important role in the teaching-learning process.